2015
DOI: 10.1016/j.scienta.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Statistical identification of chilling and heat requirements for apricot flower buds in Beijing, China

Abstract: a b s t r a c tInstead of the commonly used approach of conducting controlled experiments to estimate chilling and heat requirements (CR and HR) of fruit trees, the statistical method of Partial Least Squares (PLS) regression was applied to identify the CR and HR of apricot (Prunus armeniaca L.) in Beijing, China by correlating first flowering dates of apricot with daily chilling and heat accumulation during 1963-2010. Three common chilling models (the 0-7.2• C, Utah and Dynamic Models) and one forcing model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Hence, assessing present and future chill and heat accumulations is essential for identifying the most suitable fruit tree species for a given site, for maintaining economically viable fruit orchards, or for ensuring that detrimental impacts of climate change can be effectively lessened ( Gao et al, 2012 ). Various studies have combined chill and heat indices for studying thermal requirements of different fruit trees or for developing models of phenology ( Maulión et al, 2014 ; Fraga et al, 2015 ; Guo et al, 2015b ; Santos et al, 2017 ). Nonetheless, a comprehensive analysis of the main fresh fruit orchards in Portugal, and their relationship with chilling and forcing is still incipient.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, assessing present and future chill and heat accumulations is essential for identifying the most suitable fruit tree species for a given site, for maintaining economically viable fruit orchards, or for ensuring that detrimental impacts of climate change can be effectively lessened ( Gao et al, 2012 ). Various studies have combined chill and heat indices for studying thermal requirements of different fruit trees or for developing models of phenology ( Maulión et al, 2014 ; Fraga et al, 2015 ; Guo et al, 2015b ; Santos et al, 2017 ). Nonetheless, a comprehensive analysis of the main fresh fruit orchards in Portugal, and their relationship with chilling and forcing is still incipient.…”
Section: Introductionmentioning
confidence: 99%
“…For deciduous fruit trees, winter chill exposure is an important precondition for dormancy release and successful spring bud burst and flowering (Campoy et al ., 2012; Jones et al ., 2015). Given this climatic requirement and the prospect of increasing temperatures due to global warming, fruit trees in many regions may soon experience – or may already be experiencing – situations where their ability to overcome their state of dormancy is compromised (Luedeling et al ., 2011a; Darbyshire et al ., 2013; Guo et al ., 2015b; Campoy et al ., 2019; Rodriguez et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence suggests that dormancy‐related processes are driven mainly by thermal and photoperiodic fluctuations (Singh et al ., 2018; Tylewicz et al ., 2018; Singh et al ., 2019). In deciduous fruit and nut trees, temperature is usually considered the principal driver of dormancy and subsequent bud burst (Egea et al ., 2003; Alburquerque et al ., 2008; Cooke et al ., 2012; Laube et al ., 2014; Guo et al ., 2015b; Benmoussa et al ., 2017). Similarly, growth after bud burst seems to be mainly modulated by temperature (Kramer et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the progression from late summer and early fall to winter, temperate tree species go through a dormancy stage to survive unfavorable thermal conditions (Campoy et al, 2011b;Legave et al, 2013;Fadón and Rodrigo, 2018). Previous studies have revealed that this process is mainly regulated by thermal and photoperiodic conditions Körner, 2012, 2014;Singh et al, 2017) and that thermal conditions are central to bud dormancy and bud burst development in different fruit tree species (Egea et al, 2003;Heide, 2008Heide, , 2011Ghelardini et al, 2010;Guo et al, 2015;Benmoussa et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%